Adverse events following COVID-19 vaccination in Kwara State, North-central Nigeria. - Louis Okeibunor Odeigah; Yahkub Babatunde Mutalub; Olalekan Ayodele Agede; Ismail A Obalowu; Susan Aiyetoro; Gafar A A Jimoh (PLOS Global Public Health, 2022)
Safe and effective vaccination remains the mainstay of control of COVID-19 because there is still no universally recommended treatment. This strategy is however being threatened by vaccine hesitancy and resistance due to fear of adverse events and safety concerns. It is, therefore, necessary to study post-vaccination adverse events (AE) in various populations and geographical areas. The objective of this study was to analyze the adverse events following COVID-19 vaccination in five major immunization centers of Kwara State Nigeria. A retrospective descriptive study of the adverse events following AstraZeneca COVID-19 vaccination that were reported from five immunization centers of Kwara State, North-central Nigeria from March to July 2021 was carried out. Statistical Package for Social Science version 26 was used for analysis. Adverse event classification and severity were compared based on age, gender, and time to onset of adverse event and vaccine dose type using the Chi-square test. The incidence of COVID-19 vaccine AE was 1.6%. There was female predominance (51.6%) and a mean age of 41.6±13.7 years. Most of the AE (95.8%) were systemic and mild (81.1%) without a requirement for any therapeutic intervention. Fatal outcome was not reported in any of the AE and the time to outcome of AE was 2 days in most cases (45.3%). No significant association was found between the variables studied and the adverse event type and severity. The low incidence and mild nature of adverse events reported in this study will add to the body of knowledge regarding vaccine adverse events and may eventually impact vaccine uptake.